Across intellectual property : essays in honour of Sam Ricketson / edited by Graeme W. Austin, Andrew F. Christie, Andrew T. Kenyon, Megan Richardson. - Austin, Graeme W.; Christie, Andrew F.; Kenyon, Andrew T.; Richardson, Megan; Ricketson, Sam (Cambridge intellectual property and information law, 2020)
Using as a starting point the work of internationally-renowned Australian scholar Sam Ricketson, whose contributions to intellectual property (IP) law and practice have been extensive and richly diverse, this volume examines topical and fundamental issues from across IP law. With authors from the US, UK, Europe, Asia, Australia and New Zealand, the book is structured in four parts, which move across IP regimes, jurisdictions, disciplines and professions, addressing issues that include what exactly is protected by IP regimes; regime differences, overlaps and transplants; copyright authorship and artificial intelligence; internationalization of IP through public and private international law; IP intersections with historical and empirical research, human rights, privacy, personality and cultural identity; IP scholars and universities, and the influence of treatises and textbooks. This work should be read by anyone interested in understanding the central issues in the evolving field of IP law.